Fatores indutores e supressores da eritropoiese em caninos doentes renais crônicos - Crivellenti, Sofia Borin [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study was to evaluate bone marrow precursor cells, circulating concentrations of cytokines and hormones that can stimulate (erythropoietin and IL-3) and suppress (parathyroid hormone, IL-1β, TNF and IFN) erythropoiesis, and make their correlation with the peripheral and central erythrocyte variables. Peripheral blood samples, urine and bone marrow were obtained from 10 dogs with chronic kidney disease stage 2 (CKD2), 10 dogs with CKD stage 3 (CKD3), 10 dogs with CKD stage 4 (CKD4), and 10 healthy adult dogs (control group) for complete blood count (CBC), serum and urinary biochemical analysis, urinalysis, immunoassays and cytological analysis of bone marrow. The concentrations of erythropoiesis stimulator and suppressor factors, and cytological bone marrow results from CKD2 dogs were similar to those of the control group. This group also exhibited reticulocytosis even though not have expressed anemia, which means that extrinsic factors are early cause of blood loss or destruction of red blood cells. The anemia in dogs with CKD is related to increased parathyroid hormone and TNFα serum concentrations. The increases of such suppressor factors in association with erythroid hypoplasia are considered as part of the genesis and the aggravation of the anemic state in the end stages of CKD in dogs

Este estudo teve como objetivo a quantificação sérica de hormônios e citocinas indutores (eritropoietina e IL-3) e supressores (paratormônio, IL-1β, TNFα e IFNγ) da eritropoiese, correlacionando-os com as variáveis eritrocitárias periféricas e centrais. Amostras de sangue periférico, urina e medula óssea foram obtidas de 10 cães com doença renal crônica estádio 2 (DRC2), 10 cães com DRC estádio 3 (DRC3), 10 cães com DRC estádio 4 (DRC4) e 10 cães adultos saudáveis (grupo controle) com vistas à realização de hemograma, análise bioquímica sérica e urinária, urinálise, ensaios imunoenzimáticos e análise citológica da medula óssea. As concentrações dos fatores indutores e supressores da eritropoiese, assim como os resultados do mielograma dos cães do DRC2 assemelharam-se aos do grupo controle, e apesar de não terem manifestado anemia, a presença de reticulocitose alerta para o fato de fatores externos a medula óssea estarem precocemente causando perda ou destruição dos eritrócitos. A anemia em cães com DRC está relacionada ao aumento nas concentrações de paratormônio e TNFα, e a exacerbação dos referidos fatores supressores, bem como à hipoplasia da série eritróide, representada principalmente pela redução da população de eritroblastos policromatofílicos e ortocromáticos, constituem, parcialmente, a base da gênese e do agravamento do estado anêmico nas fases mais avançadas da DRC em cães
Keywords: Cão; Citocinas; Hormonios; Medula ossea; Eritropoese; Insuficiencia renal cronica; Cytokines